Contemporary post‐marketing adverse events and modes of failure related to VASCADE Vascular Closure System: The utility of the MAUDE database. Issue 3 (4th September 2021) - Case, Brian C.; Kumar, Sant; Medranda, Giorgio A.; Yerasi, Charan; Forrestal, Brian J.; Satler, Lowell F.; Ben‐Dor, Itsik; Hashim, Hayder; Bernardo, Nelson L.; Rogers, Toby; Waksman, Ron
Abstract: Objectives: To analyze post‐marketing surveillance data from the United States Food and Drug Administration (FDA) Manufacturer and User Facility Device Experience (MAUDE) database for the VASCADE Vascular Closure System (Cardiva Medical Inc., Santa Clara, CA). Background: The VASCADE Vascular Closure System is a closure device for femoral arterial and venous access‐site closure that was approved by the FDA in 2013. However, post‐marketing data and experience on the most commonly reported complications and modes of failure associated with the VASCADE Vascular Closure System are limited. Methods: Post‐marketing surveillance data from the FDA MAUDE database from October 2013 through March 2020 were analyzed, yielding 201 reports. Results: Of the 201 reports of major complications involving VASCADE devices, 156 reports involved either injury (145) or death (11) related to the device. Of the 145 injury reports, bleeding was the most common adverse outcome described (85), followed by pseudoaneurysm (29) and pulselessness of an extremity (21). The device malfunction incidents (41 reports) were reported in three main categories, with deployment failure being the most commonly reported complication. Conclusions: Our analysis of the MAUDE database demonstrates that in contemporary post‐marketing practice, physicians should be well‐trained and educated to use the VASCADE closure device because improper utilization is a common cause of device failure, and complications with the VASCADE device can have profound clinical implications.